Dissecting the unique role of the retinoblastoma tumor suppressor during cellular senescence - Chicas, Agustin (2010)
The RB protein family (RB, p107, p130) has overlapping and compensatory functions in cell cycle control. However, cancer-associated mutations are almost exclusively found in RB, implying that RB has a non-redundant role in tumor suppression. We demonstrate that RB preferentially associates with E2F target genes involved in DNA replication and is uniquely required to repress these genes during senescence but not other growth states. Consequently, RB loss leads to inappropriate DNA synthesis following a senescence trigger and, together with disruption of a p21-mediated cell cycle checkpoint, enables extensive proliferation and rampant genomic instability. Our results identify a non-redundant RB effector function that may contribute to tumor suppression and reveal how loss of RB and p53 cooperate to bypass senescence.